PERBEDAAN HASIL BELAJAR KELAS KONTROL DAN KELAS EKSPERIMEN MENGGUNAKAN MEDIA KUIS ADOBE FLASH CS6 - Harjanti, Diah Trismi; Ulfah, Maria; Rezeki, Galuh Sri (Universitas Tanjungpura, 2022)
This study aims to determine the differences in learning outcomes of the control class and the experimental class using the Adobe Flash CS6 quiz media. Thel type ofl research usedl is a Quasil Experiment Designl type of Nonequivalentl Control Groupl Design. Data collection techniques used are tests, observations, interviews, and documentation. The data collection instruments in this study were test sheets, observation sheets, guidelines and documentation sheets. The results of this study indicate that there are differences in the learning outcomes of students who are taught using Adobe Flash CS6-based quiz media with students who are not taught using Adobe Flash CS6-based quiz media.